Pengaruh Current Ratio, Quick Ratio, Debt To Equity Ratio Terhadap Return On Assets Pada Perusahaan Pertambangan - Wahyu Rahmah Wati (CV. ITTC INDONESIA, 2024)
This research aims to determine the effect of Current Ratio, Quick Ratio and Debt to Equity Ratio on Return On Assets in Mining Companies. With puposive sampling technique. The population that was sampled was 5 mining companies listed on Bursa Effek Indonesia in 2020-2023. The analysis method used is the panel data regression method. Testing in this study uses the Stata application version 17. The results show that partially (test T) Current Ratio, Quick Ratio and Debt to Equity Ratio have no significant effect on Return On Assets. Another research result is Simultaneously showing that (test F) or together Current Ratio, Quick Ratio and Debt to Equity Ratio do not have a significant effect on Return On Assets in Mining Companies listed on the Indonesia Effek Exchange in 2020-2023.